2009
DOI: 10.1016/j.ahj.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride/high-density lipoprotein cholesterol ratio predicts all-cause mortality in women with suspected myocardial ischemia

Abstract: High triglycerides (TG) and low high density lipoprotein cholesterol (HDL-C) are important cardiovascular risk factors in women. The prognostic utility of the TG/HDL-C ratio, a marker for insulin resistance and small dense low density lipoprotein particles, is unknown among high risk women. Methods We studied 544 women without prior myocardial infarction or coronary revascularization, referred for clinically indicated coronary angiography and enrolled in the Women’s Ischemia Syndrome Evaluation (WISE). Fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
172
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 25 publications
10
172
1
2
Order By: Relevance
“…14 -16 High TG and low HDL-C levels, which characterize the dyslipidemia of metabolic syndrome, have roles in atherosclerosis and coronary heart disease development. [16][17][18] In addition, the current study showed that obesity was a risk factor of STEMI in young patients. All these findings suggest that young patients with STEMI are more likely to meet most of the Adult Treatment Panel III criteria for metabolic syndrome, including obesity, high TG, and low HDL-C levels.…”
Section: -411supporting
confidence: 50%
“…14 -16 High TG and low HDL-C levels, which characterize the dyslipidemia of metabolic syndrome, have roles in atherosclerosis and coronary heart disease development. [16][17][18] In addition, the current study showed that obesity was a risk factor of STEMI in young patients. All these findings suggest that young patients with STEMI are more likely to meet most of the Adult Treatment Panel III criteria for metabolic syndrome, including obesity, high TG, and low HDL-C levels.…”
Section: -411supporting
confidence: 50%
“…According to the TAG/HDL-C and LDL-C/HDL-C ratios of the present study, adjustments of SLP patterns in the fibrotic rats, irrespective of the type of herbal treatment they received, indicated incidences of atherogenicity as defined elsewhere. 39,58,61,62,63 The massive disarrangement of hepatic tissues architecture of untreated fibrotic rats (Group 3) correlated with the levels of alterations of serum indicators, namely, serum ALT, AST and ALP activities as well as serum TBC as previously described. 12,13,98,99 Additionally, photomicrograph section of hepatic tissues of fibrotic rats ( Figure 6) revealed and confirmed CCl 4 -induced necrosis and steatosis as previously described.…”
Section: Discussionsupporting
confidence: 63%
“…HDL-C had a much stronger association with mortality and clinical worsening than either index, and remained significant when adjusted for both HOMA-IR and TG/HDL-C ratio. Many studies have shown that insulin resistance and the metabolic syndrome carry a higher risk of systemic cardiovascular events (30)(31)(32)(33)(34), but this is not universal (35)(36)(37)(38)(39). In one study (32) cardiovascular events were more closely dependent on insulin resistance than HDL-C levels, whereas another study suggested that HDL-C was the better predictor (37).…”
Section: Discussionmentioning
confidence: 99%